Analysis of bicarbonate, phosphate and other anions in saliva by capillary electrophoresis with capacitively coupled contactless conductivity detection in diagnostics of gastroesophageal reflux disease. Issue 1 (8th November 2019) - Dosedělová, Věra; Ďurč, Pavol; Dolina, Jiří; Konečný, Štefan; Foret, František; Kubáň, Petr
Abstract: Bicarbonate and phosphate constitute major salivary buffering components, and their importance consists in the neutralization of acidic gastric contents during reflux episodes. In this work, capillary electrophoresis with capacitively coupled contactless conductivity detector was applied for the analysis of bicarbonate, phosphate, and another inorganic (chloride, nitrite, nitrate, sulfate, thiocyanate) and organic anions (acetate, butyrate) to evaluate their levels in saliva. The background electrolytes of different composition and pH between 6.02–9.41 were assessed for the bicarbonate and phosphate determination by comparison of the real analyses of a model solution with the simulation by PeakMaster software. The optimized background electrolyte was composed of 10 mM 2‐(N‐morpholino)ethanesulfonic acid, 20 mM arginine, and 30 µM cetyltrimethylammonium bromide, pH 8.95. Using this BGE, the anion levels were compared in saliva from 20 patients suffering from gastroesophageal reflux disease (GERD) and saliva from 12 healthy subjects. Bicarbonate levels were significantly elevated in saliva from GERD patients suggesting the possible applicability of bicarbonate as a biomarker in non‐invasive diagnostics of GERD by CE‐C 4 D.